Students’ Learning Styles: an Ethnographic Case Study at UIN Walisongo Semarang - Muhammad Nafi Annury (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2016)
This research is aimed to know what kinds of learning preferences are students intended most? And how many types of learners’ characteristics appear in ELT classrooms? This research was conducted through qualitative approach. This means that the data are collected not in the form of numbers, the data are taken from questionnaires, documentation, and observation. The results of this study are as follows: students of ELT program at UIN Walisongo Semarang tend to study by various kind of learning. It can be proved that First, regarding to the description of 2A class which has 11.2% visual students, 16.02% of audio-lingual, 5% kinaesthetic and 14.11% are others, would use multimedia which is available in the classroom. Whereas, the description of 2B class has shown that 13% students are visual learners, 11% audio-lingual learners, 6.72% kinaesthetic and 13,72% are others. Last but not least, there are 12% visual learners, 11.17% audio-lingual, 7.25 kinaesthetic and the rest 14% others. Furthermore, there are four characteristics which appear from the research, they are as follows: visual learners, auditory learners, kinaesthetic learners, and other characteristics